REFERRING TO SPEECH ACT OF GRATITUDE IN COMMUNICATION - Abidova Rokhatoy Khudayberganovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article will focus on the analysis of one of the most common events - gratitude in natural communication in English and Uzbek. Hence, the verbal event of gratitude belongs to the sphere of phatic communication and has many of the characteristics of a communicative ritual, the main social purpose of which is to establish a friendly atmosphere between the participants of the interaction.